T-pattern detection in the scientific literature of this century: A systematic review - Anguera, M. Teresa; Jonsson, Gudberg K.; Escolano-Pérez, Elena; Sánchez-Lopez, Carmen Rosa; Losada, José Luis; Portell, Mariona (Frontiers in Psychology, 2023)
Introduction Scientific literature contains mainly systematic reviews focused on substantial aspects, but there are also approaches that have combined both substantial and methodological aspects, which is our preferred option since it undeniably adds value. The aims of this study were: (1) to carry out a systematic review of the literatura on T-Pattern analysis (TPA), and (2) to explore the possible contribution of mixed methods research to the integration of qualitative and quantitative elements on a synthesis level. Methods Based on PRISMA guidelines, searches were carried out in the Scopus, PsycINFO, and Web of Science databases. The general search syntax was: “THEME” AND (“T-Patterns” OR “T Patterns”) carried out in title, keywords and abstract. In addition, we included empirical articles on THEME and T-Patterns collected in other sources based on citations in several empirical works and consultations with different authors. This selection process resulted in 125 primary documents making up this systematic review. Results The results showed that the detection of structures in behavior patterns forms a nexus between studies carried out in very diverse fields and contexts. Most studies are observational, whilst the applicability and power of T-Pattern detection are extraordinary. It allows the researcher to go deeper in a robust analysis that responds to the integration of qualitative and quantitative elements which constitutes the leit motive of mixed methods; and also to discover the deep, hidden structure that underlies the respective databases, regardless of the methodology used in each study. The possibilities in assigning parameters notably increase the options for obtaining results and their interpretation. Discussion It is relevant the extraordinary strength and applicability of T-pattern detection. There is a high presence of T-pattern detection and analysis in studies using observational methodology. It is necessary commit to consolidating the methodological analysis of selected works, as taking individual and collective responsibility for improving methodological quality of TPA studies, taking advantage of the resources provided by the THEME program.